Academic Resilience in Chemistry during Covid-19: A Systematic Review - Desfi Annisa; Hari Sutrisno; Endang Widjajanti (Jurnal Penelitian Pendidikan IPA, 2023)
The number of difficulties experienced by students in online learning during a pandemic such as lack of focus and motivation due to stress, students experience a decline and involvement in learning. Some students stated the lack of access to technology and the environment was not conducive to learning. Students who cannot overcome academic difficulties are familiar with academic resilience. This study aimed to review articles on student academic resilience during the COVID-19 pandemic in chemistry lessons. This research is systematic research using the PRISMA method. The systematic review used articles from the range 2020-2023 published in PubMed, Google Scholar, and Science Direct. A total of 4 articles on the resilience of students studying chemistry during the COVID-19 pandemic met the inclusion criteria. The results showed that journals discussing student resilience in studying chemistry during the COVID-19 pandemic were still limited. However, from this literature research, it turns out that academic resilience is considered capable of maintaining learning success in students during the COVID-19 pandemic